Oral mucosal changes caused by nicotine pouches: case series - Sintija Miluna-Meldere; Sarlote Agate Vanka; Ingus Skadins; Juta Kroica; Maris Sperga; Dagnija Rostoka (Diagnostic Pathology)
Abstract Oral nicotine pouches are the latest products in the tobacco industry. They are manufactured by large tobacco companies and entice tobacco or nicotine addicts, although the products are presented as a ‘harmless choice.’ Nevertheless, dentists and oral health specialists worry about oral mucosal changes due to product interactions with the oral mucosa. Unfortunately, there are no case reports of oral mucosal changes from nicotine pouches that are also investigated histopathologically. The aim of the present study was to visually and histopathologically investigate oral mucosal changes in nicotine pouch users. An online retrospective survey regarding medical and dental health, dietary habits, and tobacco consumption habits was conducted (n = 50). Respondents were selected for further intraoral and histopathological investigation based on the inclusion criteria. All five respondents had oral lesions that were histopathologically analyzed. Visually, the lesions varied in form and intensity, but all appeared white at the location where the pouches were placed. Histopathological analyses revealed parakeratosis with acanthotic epithelium, intraepithelial and connective tissue oedema, and chronic inflammatory infiltration with lymphocytes and macrophages. Participants received information about nicotine cessation and oral health recommendations. In conclusion, nicotine pouches significantly impacted oral mucosa with white lesions that revealed important changes at the cellular level.